The general equation of shell expansion under the action of high pressure - Popov Alexander; Valiev Rustem (BIO Web of Conferences)
The task of determining the discharge speed of the shell breakage elements is of important application. Information on the flight speed allows you to evaluate the reliability of the structure in extreme situations. The solution of this problem presents certain difficulties associated with the non-stationary process of destruction of the shell in question.